Seedling structure in Asteraceae weedy species: considerations on the vasculature system - Santos, Luciane da Silva; Dariva, Higor Simionato; Muller, Rafael Hespanhol; Garcia de Almeida, Odair Jose [UNESP]; Souza, L. A. de (Soc Botanica Sao Paulo, 2014)
Seedling structure in Asteraceae weedy species: considerations on the vasculature system. The vasculature system of the seedling is of interest since it represents the first mature vascular coordination between shoot and root, which was foreshadowed in the procambial system of the embryo. In this study, seedlings of ten Asteraceae weedy species were analyzed focusing on the vasculature system using a morpho and anatomical approach. The roots were found to be diarch and tetrarch, the species have intermediate or high root/shoot transition, and the cotyledons develop an independent double leaf-trace and a common simple-leaf trace. The transition region of the seedlings is strikingly different when compared with other families, such as, Annonaceae, Cactaceae, Fabaceae, Myrtaceae, Amaranthaceae, Clusiaceae, and Rutaceae. In spite of the uniformity in the vascular arrangement among the Asteraceae seedlings, the conclusion attained from this study is that some essential structural details may be of diagnostic value, such as the stele arrangement, the level of the transition zone, the cotyledon sheath, and the splitting of the phloem. Further, the presence of trilacunar node in the Asteraceae can be the result of a reversal evolutionary process ( homoplasy) during the life history of the family.
Keywords: Cotyledonary node; Hypocotyl; Root; Seedling anatomy; Trilacunar node; Vascular arrangement